Filsafat Pendidikan Islam dalam Pemikiran Imam Al-Ghazali: Kajian tentang Tujuan, Kurikulum, dan Metode Pendidikan - Subhanal Hanafi; Muhksin Achmad (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
This study examines the philosophy of Islamic education in the thought of Imam Al-Ghazali, focusing on educational objectives, philosophical foundations, curriculum, educational methods, and their relevance to contemporary education. Al-Ghazali views education as an integral process that is not merely oriented toward intellectual development, but also toward moral formation and the purification of the soul in order to attain true happiness (Sa‘adah) in both worldly life and the hereafter. This research employs a descriptive qualitative approach through library research by analyzing Al-Ghazali’s major works, such as Ihya’ ‘Ulum al-Din, Ayyuha al-Walad, and Mizan al-‘Amal, as well as relevant supporting literature. The findings indicate that Al-Ghazali rejects the dichotomy between religious and worldly sciences, as reflected in his concept of fard ‘ain and fard kifayah, which are complementary and interconnected. His educational curriculum is integrative and oriented toward public benefit, while his educational methods emphasize habituation, exemplary conduct of educators, and the process of Tazkiyat Al-Nafs (self-purification). Al-Ghazali’s educational philosophy remains relevant in addressing contemporary moral crises by offering a philosophical foundation for forming the insan kamil a complete human being who is intellectually knowledgeable, morally upright, and spiritually grounded.